Migration and Education Decisions in a Dynamic General Equilibrium Framework - Dessus, Sebastien (World Bank, Washington, DC, 2012)
With growing international skilled labor mobility, education and migration decisions have become increasingly inter-related, and potentially have a large impact on the growth trajectories of source countries, through their effects on labor supply, savings, or the cost of education. The authors develop a generic dynamic general equilibrium model to analyze the education-migration nexus in a consistent framework. They use the model as a laboratory to test empirical conditions for the existence of net brain gain, that is, greater domestic accumulation of human capital (in per capita terms) with greater migration of skilled workers. The results suggest that although some structural parameters can favor simultaneously greater human capital accumulation and greater skilled migration - such as high ratio of remittances over domestic incomes, high dependency ratios in migrant households, low dependency ratios in source countries, increasing returns to scale in the education sector, technological transfers and export market access with Diasporas, and efficient financial markets - this does not necessarily mean that greater migration encourages the constitution of greater stocks of human capital in source countries.